Aplicaciones de la metodología TRIZ en el diseño ergonómico de estaciones de trabajo - Henrich Saavedra, Marco (2013)
The present paper is introducing TRIZ as a methodological tool that can be applied in the solution of ergonomic problems. The applicability of 6 of the TRIZ principles is analyzed like base to find creative solutions to ergonomic problems, such as design of workstations, noise and lighting, among others.